Treasury diagnostic toolkit - Hashim, Ali; Moon, Allister J.; ebrary, Inc. (Washington, DC : World Bank, 2004)
Treasury Diagnostic Toolkit is part of the World Bank Working Paper series. These papers are published to communicate the results of the Bank's ongoing research and to stimulate public discussion. Improvement in the management of public finances in developing countries has been an increasingly important focus of World Bank and IMF assistance to member countries. A key element of such assistance is the development of effective treasury systems, which form the backbone for recording and processing all financial transactions related to government budgets. The establishment of an effective, integrated treasury system helps manage public monies with greater financial control, improved monitoring, better planning, better fiscal reporting, and better data for budget formulation, while also improving transparency and accountability of government. This toolkit consists of three parts: (1) a treasury systems questionnaire to be used as a diagnostic tool in assessing the status of treasury functions, (2) a costing model using information in the aforementioned questionnaire to estimate the likely costs of a comprehensive investment program, and (3) an application software questionnaire intended to help managers select appropriate application software, focusing on treasury-specific requirements.
World Bank Working Paper No.19
Includes bibliographical references.
aia 9/9/16
Loans
Keywords: Finance, Public; Government financial institutions; Finance, Public $1 (BHandbooks, manuals, etc.s